Effects of poultry litter biochar on soil enzyme activities and tomato, pepper and lettuce plants growth - Muhittin Onur Akça; Ayten Namlı (Eurasian Journal of Soil Science, 2015)
Biochar application to soils is being considered as a means to sequester carbon (C) while concurrently improving soil functions. A greenhouse experiment was carried out to determine the effects of biochar from the pyrolysis poultry litter (PL) on the soil enzyme activities, organic matter content and growth of tomato, pepper and lettuce plants. In the experiment, the combination of 15.15.15 composite fertilizer with 0, 200, 400 and 600kg/da doses of PL biochar were applied into the clay loam soil. Compared to the control and chemical fertilizer alone, the soil organic matter was significantly increased after biochar amendments. β-glucosidase, alkaline phosphatase, urease and arylsulphatase enzyme activities in soils were increased by the biochar applications significantly (P<0.05). Plant fresh and dry weight of tomato, pepper and lettuce plants were higher in 4kg/ha PL biochar treatment than in the other treatments. The results showed that PL biochar amendment to soils in the agricultural use increased yield of plants and enzyme activities with increasing soil organic matter content as well as improving soil properties.